The Influence of Peer Teaching Method on Speaking Skills of Eight Grade Student at Abdullah Bin Mas'ud Boarding School, Kisaran - Ibnul Fath, Umeir; Hudzaifah, Hudzaifah (Universitas Islam Tribakti Lirboyo, Kediri, 2025)
Arabic is a foreign language that holds an important position in Islamic education in Indonesia, particularly within the environment of Islamic boarding schools (pesantren). Although it has become part of the official curriculum, the teaching of speaking skills (kalam) often encounters obstacles, both in terms of teaching methods and students' active engagement. In this context, the present study proposes the Peer Teaching method as an alternative approach aligned with Vygotsky’s social constructivism theory, particularly the concept of the Zone of Proximal Development (ZPD), which emphasizes learning through peer interaction. This research was conducted in the second-grade Mutawassith class at the Abdullah Bin Mas’ud Islamic Boarding School in Kisaran. The aim of this study is to analyze the change in students' speaking ability before and after the treatment and to assess the effectiveness of the peer teaching method in the pesantren learning context. A quantitative approach was employed using a one-group pre-experimental design (One Group Pretest-Posttest). The results showed that the total pretest score was 1,646 with an average of 65.84, while the posttest score increased to 2,151 with an average of 86.04. Statistical testing revealed that the calculated t-value was greater than the critical t-value (2.797 < 8.283 > 2.064), indicating a significant influence of the peer teaching method on improving students' speaking ability. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This study provides practical contributions to the development of speaking (kalam) instructional methods in pesantren and other Islamic educational institutions. The use of peer teaching not only improves learning outcomes quantitatively but also fosters active participation, self-confidence, and collaboration among students. With a strong theoretical foundation and significant empirical findings, this method can serve as an innovative alternative to overcome stagnation in spoken Arabic instruction, particularly in pesantren environments characterized by collective and interactive learning cultures.